Astrophysics Source Code Library: ASCL.net : making codes discoverable since 1999 (ASCL at Michigan Technological University, 1999)
"The Astrophysics Source Code Library (ASCL) is a free online registry for source codes of interest to astronomers and astrophysicists and lists codes that have been used in research that has appeared in, or been submitted to, peer-reviewed publications."
Gesehen am 28.09.2017
Keywords: Datenbank